Local Muscle Fatigue and 3D Kinematics of the Cervical Spine in Healthy Subjects. Issue 2 (3rd March 2016) - Niederer, Daniel; Vogt, Lutz; Pippig, Torsten; Wall, Rudolf; Banzer, Winfried
ABSTRACT: The authors aimed to further explore the effects of local muscle fatigue on cervical 3D kinematics and the interrelationship between these kinematic characteristics and local muscle endurance capacity in the unimpaired cervical spine. Twenty healthy subjects (38 ± 10 years; 5 women) performed 2 × 10 maximal cervical flexion–extension movements. Isometric muscle endurance tests (prone/supine lying) were applied between sets to induce local muscle fatigue quantified by Borg scale rates of perceived exertion (RPE) and slope in mean power frequency (MPF; surface electromyography; m. sternocleidomastoideus, m. splenius capitis). Cervical motion characteristics (maximal range of motion [ROM], coefficient of variation of the 10 repetitive movements, mean angular velocity, conjunct movements in transversal and frontal plane) were calculated from raw 3D ultrasonic movement data. Average isometric strength testing duration for flexion and extension correlated to the cervical ROM ( r = .49/ r = .48; p < .05). However, Student's t test demonstrated no significant alterations in any kinematic parameter following local muscle fatigue ( p > .05). Although subjects' cervical muscle endurance capacity and motor output seems to be conjugated, no impact of local cervical muscle fatigue on motor function was shown. These findings underline the importance of complementary measures to address muscular performance and kinematic characteristics in outcome assessment and functional rehabilitation of the cervical spine.